Physcion and Physcion 8-O-β-D-glucopyranoside: Natural Anthraquinones with Potential Anticancer Activities - Adnan, Muhammad; Rasul, Azhar; Hussain, Ghulam; Shah, Muhammad A.; Sarfraz, Iqra; Nageen, Bushra; Riaz, Ammara; Khalid, Rida; Asrar, Muhammad; Selamoglu, Zeliha; Adem, Şevki; Sarker, Satyajit D. (Current Drug Targets, 2021)
Nature has provided prodigious reservoirs of pharmacologically active compounds for drug development since times. Physcion and physcion 8-O-β-D-glucopyranoside (PG) are bioactive natural anthraquinones which exert anti-inflammatory and anticancer properties with minimum or no adverse effects. Moreover, physcion also exhibits anti-microbial and hepatoprotective properties, while PG is known to have anti-sepsis as well as ameliorative activities against dementia. This review aims to highlight the natural sources and anticancer activities of physcion and PG, along with associated mechanisms of actions. On the basis of the literature, physcion and PG regulate multitudinous cell signaling pathways through the modulation of various regulators of cell cycle, protein kinases, microRNAs, transcriptional factors, and apoptosis linked proteins resulting in the effective killing of cancerous cells in vitro as well as in vivo. Both compounds effectively suppress metastasis, furthermore, physcion acts as an inhibitor of 6PGD and also plays an important role in chemosensitization. This review article suggests that physcion and PG are potent anticancer drug candidates, but further investigations on their mechanism of action and pre-clinical trials are mandatory in order to comprehend the full potential of these natural cancer killers in anticancer remedies.
Keywords: chemosensitization